WAGE DETERMINATION IN THE DOMESTIC SERVICES SECTOR IN KAHAWA AND GITHURAI ESTATES IN KIAMBU COUNTY, KENYA - Okemwa, Josephat Mongare; Korir, Dr.Julius (International Journal of Economics, 2018)
Purpose: To establish underlying factors that influence wage determination in the domestic service sector in Kahawa and Githurai estates in Kiambu County, Kenya. Methodology: The study used a descriptive cross-sectional survey design which sought to give the quantitative relationship between the wage and its determinants. Primary data was collected by interviewers using questionnaires from which 367 domestic workers were randomly selected and interrogated. The collected data was coded and quantitatively analysed using robust regression. Findings: The results of the analysis indicate that education level in years of schooling, work experience in years, type of residence are important factors in wage determination in the domestic services sector. Sex and dwelling of a domestic worker were found not important factors in determining wages. Unique contribution to theory, practice and policy: The implications of the findings suggest that in an effort to create fairness in the domestic services sector, policies and strategies that are anchored in the social economic characteristics of a domestic worker as well as human capital investment should be considered in determining domestic worker's wages a part from minimum wages which is generally defined and regulated by state law.